2018
DOI: 10.1063/1.5051546
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric polynomials, generalized Jacobi-Trudi identities and τ-functions

Abstract: An element [Φ] ∈ Gr n (H + , F) of the Grassmannian of n-dimensional subspaces of the Hardy space H + = H 2 , extended over the field F = C(x 1 , . . . , x n ), may be associated to any polynomial basis, labelled by partitions λ, provide an analog of Jacobi's bi-alternant formula, defining a generalization of Schur polynomials. Applying the recursion relations satisfied by the polynomial system φ to the analog {h (0) i } of the complete symmetric functions generates a doubly infinite matrix h (j) * Work of J.H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…It seems that this simple fact is generally overlooked in the literature, though several papers can be named, where versions of Jacobi-Trudi identities are applied: (see e.g. [1,11] where variations of Jacobi -Trudi identities are used for construction of τ -functions). Note that, as we show below, the so-called Giambelli identity in a general form is equivalent to a general Jacobi -Trudi identity statement.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that this simple fact is generally overlooked in the literature, though several papers can be named, where versions of Jacobi-Trudi identities are applied: (see e.g. [1,11] where variations of Jacobi -Trudi identities are used for construction of τ -functions). Note that, as we show below, the so-called Giambelli identity in a general form is equivalent to a general Jacobi -Trudi identity statement.…”
Section: Introductionmentioning
confidence: 99%
“…if we denote the Young diagram by λ = (α 1 , · · · , α r |β 1 , · · · , β r ). These formulas were originally found for the Schur polynomial, though it turns out that they appear naturally in integrable systems [17][18][19][20]. Hence, in this context, it is natural to ask what the integrable structure for the ABJM matrix model is.…”
Section: Abjm Matrix Modelmentioning
confidence: 99%
“…After introducing the grand canonical ensemble 18) it was found that the normalized grand canonical two-point functions…”
Section: Abjm Matrix Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…with H = H M =0 . 4 In [29] the Jacobi-Trudi identity is defined also by extending the matrix size in (1.10) to be greater than L. Since this extension does not make any differences essentially, we restrict the matrix size to be L. The Jacobi-Trudi identity defined with the automorphism ϕ plays an important role in the study of integrable models and is also called the quantum Jacobi-Trudi identity (see [4,12,23,26,27,42,43,48] for examples).…”
Section: )mentioning
confidence: 99%